2016
DOI: 10.1007/s10661-016-5545-3
|View full text |Cite
|
Sign up to set email alerts
|

Land use effect on invertebrate assemblages in Pampasic streams (Buenos Aires, Argentina)

Abstract: Agriculture and livestock may contribute to water quality degradation in adjacent waterbodies and produce changes in the resident invertebrate composition. The objective of the present study was to assess land use effects on the stream invertebrate assemblages in rural areas of the Argentine Pampa. The four sampling events were performed at six sites in four streams of the Pampa plain; two streams were sampled inside a biosphere reserve, and another one was surrounded by extensive livestock fields. The fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
1
8
0
8
Order By: Relevance
“…Mugni et al (2013) measured higher nutrient concentrations in a stream surrounded by a recently fertilized crop than in the same stream when that crop was not being fertilized. The nutrient concentrations in the present study revealed a wide variability, likewise reported in previous publications (e.g., Mugni et al, 2013;Solis et al, 2016Solis et al, , 2017.…”
Section: Macroinvertebrate Assemblagessupporting
confidence: 90%
See 1 more Smart Citation
“…Mugni et al (2013) measured higher nutrient concentrations in a stream surrounded by a recently fertilized crop than in the same stream when that crop was not being fertilized. The nutrient concentrations in the present study revealed a wide variability, likewise reported in previous publications (e.g., Mugni et al, 2013;Solis et al, 2016Solis et al, , 2017.…”
Section: Macroinvertebrate Assemblagessupporting
confidence: 90%
“…Agricultural land use affects macroinvertebrate assemblages in regional streams, resulting in the disappearance or decreased abundance of sensitive groups such as Odonata and Ephemeroptera (Jergentz et al, 2004) or Amphipoda (Solis et al, 2016). Agricultural land use has been found to increase nutrient concentrations in pampean streams (Mugni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, amphipods are model species for this type of toxicity bioassay (USEPA, 2000). Hyalella curvispina is a native South American species found in streams in the study area (Ronco et al, 2008) but not in areas impacted by agricultural activity (Solis et al, 2016), suggesting that it is a species sensitive to the presence of pesticides in sediments (Jergentz et al, 2005;Phillips et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…Este enfoque asume que la composición del ensamble funciona como bioindicador reflejando el estado de un cuerpo de agua (Rosenberg & Resch, 1993;Hering et al, 2004). En nuestro medio, varios autores enfocaron el estudio de los ensambles de invertebrados como bioindicadores de calidad de aguas y la aplicación de índices bióticos para detectar variados impactos, desde contaminación industrial (Gomez et al, 2008), el efecto del uso del suelo (Miserendino & Pizzolón, 1999;Rodrigues-Capítulo et al, 2001;Corigliano et al, 2005;Miserendino et al, 2008;Miserendino et al, 2011;Solis et al, 2016;Solis et al, 2017) como así también por distintos tipos de hábitats (Velasquez & Miserendino, 2003). Domínguez & Fernández (1998) determinaron el estado de los ríos de Tucumán en base a su fauna bentónica.…”
Section: Introductionunclassified